Resistência de união de bráquetes ortodônticos aderidos à cerâmica - Di Guida, Luís Antônio (2015)
The great demand for orthodontic treatment in adults, requires adhesion of brackets to enamel and other substrates. This study evaluated the bond strength ( ) to dental ceramics, for minor damage on treatment outcomes. Two hundred and forty ceramic specimens (IPS e-max CAD) were divided into twelve experimental groups (n = 20). Two ceramic brackets (monocrystalline and polycrystalline alumina) and a metal bracket were used for orthodontic bonding, after one of the following ceramic surface treatment:(1) 60 s-hydrofluoric acid (HF); (2) silane (S) agent application / 3 min, (3) HF followed by S; (4) MDP application. After the shear test, fractographic analysis was performed using optical microscopy (OM) and scanning electron microscopy (SEM). The monocrystalline ceramic bracket (BCm) bonded with resin cement to dental ceramics treated with (HF) followed by (s), or HF only showed the highest values). In contrast, the polycrystalline ceramic bracket (BCp) bonded to dental ceramic treated with adhesive system containing MDP monomer had the lowest value of , that was not different statistically from the other groups treated with MDP, and they did not produce enough to bond brackets to dental ceramics. The adhesive treatment for bonding brackets in ceramic surfaces requires proper treatment, with micromechanical retention from HF prior to orthodontic bonding. When there is a need for higher in areas of higher masticatory stress, the HF should be associated with the organosilane.